Molecular Diversity of Rhizobia Occurring on Native Shrubby Legumes in Southeastern Australia - Lafay, Bénédicte (American Society for Microbiology, 1998)
The structure of rhizobial communities nodulating native shrubby legumes in open eucalypt forest of southeastern Australia was investigated by a molecular approach. Twenty-one genomic species were characterized by small-subunit ribosomal DNA PCR-restriction fragment length polymorphism and phylogenetic analyses, among 745 rhizobial strains isolated from nodules sampled on 32 different legume host species at 12 sites. Among these rhizobial genomic species, 16 belonged to the Bradyrhizobium subgroup, 2 to the Rhizobium leguminosarum subgroup, and 3 to the Mesorhizobium subgroup. Only one genomic species corresponded to a known species (Rhizobium tropici). The distribution of the various genomic species was highly unbalanced among the 745 isolates, legume hosts, and sites. Bradyrhizobium species were by far the most abundant, and Rhizobium tropici dominated among the Rhizobium and Mesorhizobium isolates in the generally acid soils where nodules were collected. Although a statistically significant association occurred between the eight most common genomic species and the 32 hosts, there was sufficient overlap in distributions that no clear specificity between rhizobial genomic species and legume taxa was observed. However, for three legume species, some preference for particular genomic species was suggested. Similarly, no geographical partitioning was found.